Reconnecter villes et campagnes : vers des symbioses agricoles et agri-urbaines ? Une exploration sur le plateau de Saclay - Caroline Petit (Éditions en environnement VertigO, 2018)
Since the 1970s, new concepts have been beginning to emerge to recreate synergies between town and agriculture, the latest of them promoting the development of a circular economy. This article centres on the transit flows within agri-food systems, considering food items, the upstream flows of farming production associated with agricultural supplies, and downstream flows corresponding to waste management. A joint approach in territorial ecology and territorial agronomy was implemented in an urban agricultural territory of the Île-de-France region, the Saclay plateau, to study agricultural and agri urban symbioses, to clarify the logics underlying flows of materials and to explore the room for manœuvre which might enable the agri-food metabolism to become increasingly internalised. The results show that internal flows and recycling loops come mainly from farms with a diversified typology : mixed-livestock farms, farms using agricultural composts, and organic farming. They also show that the system as a whole is still marked by a linear, externalised operation. Different ways are envisaged to set up more agricultural and agri-urban symbioses, all of them requiring technological, organisational and cultural changes at different levels. The assessment of the sustainability of these local flows must necessarily integrate quantitative aspects, for which we propose here a methodological approach. But it must also include qualitative aspects in order to consider the nature of the materials in circulation and the possible contamination of the recycling loops.